Writing feminity: case of Anastasia - Caune, Evija (Cuestiones de Género: de la igualdad y la diferencia, 2008)
The case of a woman who wanted to sell her daughter on Internet and following lawsuit is explored in the article. The author analyzes this case as an artefact; she investigates how the story about condemned woman is constructed in the mass media. The author dissociates from what has actually happened, paying attention to the narrative about Anastasija who is shaped as a person, woman, and mother, while both creating and reproducing conceptions, unwritten behaviour imperatives for sex category and social roles. The contradiction of the factual trial and society`s conceptions about “correct” performance of gender and mother role is exam.